Polyamine-induced somatic embryogenesis and plantlet regeneration in vitro from plumular explants of dwarf cultivars of coconut (Cocos nucifera) - K, RAJESH M; E, RADHA; K, SAJINI K; KARUN, ANITHA (The Indian Journal of Agricultural Sciences, 2014)
Regeneration of complete plantlets via organogenesis and somatic embryogenesis was achieved from plumular tissues of two dwarf cultivars of coconut, viz. Chowghat Green Dwarf (CGD) and Malayan Yellow Dwarf (MYD). Significant differences were noticed between varieties for the formation of embryogenic calli. There were also significant differences for interaction between variety and regeneration medium with respect to formation of somatic embryos. Well developed plantlets were acclimatized under green house conditions and then successfully established in the field. The development of an efficient method of cloning coconut using plumular explants (with more rapid development of calli and somatic embryos and greater frequencies of plant regeneration compared with calli from inflorescence or leaf tissues) offers a potential for the development of a long-term in vitro means of conserving significant coconut germplasm by cryopreservation of plumular explants. Mass multiplication of elite palms selected on the basis of resistance to root (wilt) diseases of coconut is possible using plumular explants. Plumule cultures can be used for rapid multiplication of proven coconut hybrids. This study can also form a model for future regeneration studies from adult tissues of coconut.